PENETAPAN KADAR ß-KAROTEN PADA BEBERAPA JENIS CABE (Genus Capsicum) DENGAN METODE SPEKTROFOTOMETRI TAMPAK - Tri Octaviani; Any Guntarti; Hari Susanti (Universitas Ahmad Dahlan, 2014)
Beta carotene is provitamin essential role for vitamin A formation. Most of vitamin A sources are ß-carotene. In the body, ß-carotene will be converted into vitamin A. Chilies are considered as one of the essential food. Chillies are known as very good sources of ß-carotene. Therefore, it is important to conduct a research in order to observe the content of ß-carotene in the chillies using visible spectrophotometry. Fresh chillies were extracted with a mixture of hexane:acetone:ethanol (2:1:1) v/v using a maceration method. After the extraction process was complete, aquabidest was added. The extraction result was non-polar phase. It was separated and evaporated. The residue was further subjected to qualitative and quantitative analysis 102 Pharmaҫiana, Vol. 4, No. 2, 2014: 101-109 obtained. Qualitative analysis by using Carr-Price method. Determination of ß-carotene was conducted using visible spectrophotometry method at 452,4 nm. The qualitative test results showed that the Capsicum annuum L. Var. abreviatum Fingerhuth, Capsicum annuum L. Var. Longum sendt) and Capsicum frutescens L. contain ß-carotene. From the research, it was obtained that the average levels of ß-carotene on the Capsicum annuum L. Var. abreviatum Fingerhuth was (10,54±0,07) mg/100g, Capsicum annuum L. Var. Longum sendt was (5,57±0,13) mg/100g and Capsicum frutescens L. was about (0,36±0,01) mg/100g. Statistical analysis using LSD test of ß-carotene levels in the Capsicum annuum L. Var. abreviatum Fingerhuth, Capsicum annuum L. Var. Longum sendt) and Capsicum frutescens L. were significantly different at P of 0.05.